Edukasi Hukum dan Pemberdayaan Komunitas Berbasis Lokal dalam Mewujudkan Perlindungan Anak dan Perempuan dari Tindak Kekerasan di Tingkat Desa Kabupaten Indragiri Hilir - Siti Rahmah; Triyana Syahfitri; Herdiansyah; Darmiwati; Sri Hidayanti; Feni Puspitasari (Indra Institute Research & Publication, 2025)
Violence against women and children remains a pressing social issue, particularly in rural areas where access to legal services and information is limited. This community engagement activity aimed to enhance legal awareness and empower local communities in preventing and addressing acts of violence through legal education and grassroots empowerment. The study employed a participatory qualitative approach integrated into a legal outreach program conducted in Teluk Dalam Village, Kuala Indragiri District, Indragiri Hilir Regency. Methods included field observation, interactive lectures, and participatory evaluation. The results showed a significant improvement in participants' understanding of legal rights, types of violence, and reporting mechanisms. Active community participation in discussions and reflections indicated a shift in perception, where violence was no longer seen as tolerable but as a violation requiring action. The conclusion of this activity emphasizes that community-based legal education is an effective strategy for building legal awareness and strengthening local protection systems for vulnerable groups.